Prenatal Learning and Memory: Review on the Impact of Exposure - Kumar, Nitesh; Kamath, Sushmitha; Kumar, Gautam; Vaishali, K.; Sinha, Mukesh K.; Amin, Revati; Chamallamudi, Mallikarjuna Rao (Current Pediatric Reviews, 2023)
Background: Prenatal Learning is a topic still debated for its existence, although the concept is well known since ancient times. Objective: The present review highlights the impact of various stimuli on learning and memory in prenatal and postnatal life. Methods: For review, various articles from preclinical and clinical studies providing early pieces of evidence of prenatal learning to date were included based on the relevancy of the databases, namely, Scopus, Pubmed, and Google Scholar. Results: Learning is the process of acquiring skills/ preferences/ habits from the experiences of the exposures of the past. These exposures are the stimuli, which help in categorizing learning into associated or nonassociated learning. The stimuli of adults related to auditory, gustatory, olfactory, visual, touch, etc. are also accessible to the prenatal life in utero either directly or indirectly through the mother. The effects of these stimuli are remarkable during prenatal life and can be seen clearly in infants. These stimuli play an important role in prenatal learning and contribute to neuronal development. The present review summarizes the pieces of evidence for each of these types of learning & their impact on the ex utero life, a futuristic view & the scope of understanding prenatal learning. The review also elucidates the factors affecting prenatal learning. Conclusion: Studies from clinical and preclinical studies reflected the impacts of several aspects of an infant’s life and the memory created during prenatal life was found to be most likely carried on to postnatal life.
Keywords: Prenatal learning